Patient satisfaction in out-of-hospital emergency care: a multicentre survey. (October 2016) - Neumayr, Agnes; Gnirke, André; Schaeuble, Joerg C.; Ganter, Michael T.; Sparr, Harald; Zoll, Adolf; Schinnerl, Adolf; Nuebling, Matthias; Heidegger, Thomas; Baubin, Michael
Abstract : Background: There is only limited information on patient satisfaction with emergency medical services (EMS). The aim of this multicentre survey was to evaluate patient satisfaction in five out-of-hospital physician-based EMS in Austria and Switzerland. Methods: The psychometrically tested and standardized questionnaire 'patient satisfaction in out-of-hospital emergency care' was used for this survey. The recruitment of the patients was carried out on the basis of inclusion and exclusion criteria. All questionnaires were sent together with an invitation letter and a prepaid return envelope, followed by a reminder 2 weeks later. The descriptive statistical analysis was carried out by an external organization to maintain anonymity. Results: The response rate of all EMS was 46.7%. High satisfaction rates were achieved for the four quality scales 'emergency call, emergency treatment, transport and hospital admission'. A significant difference was found between the Swiss and the Austrian dispatch centres in the judgement of the call takers' social skills. Patient satisfaction with the emergency treatment, for example, reduction of pain, was high in all EMS, independent of whether the EMS is physician (Austria) or physician and emergency medical assistant based (Switzerland). Lowest satisfaction rates were found for items of social skills. Conclusion: Patient satisfaction in out-of-hospital physician-based EMS is generally high. There is room for improvement in areas such as the social skills of dispatchers and EMS-team members and the comfort of the patients during transport. A checklist should be developed for basic articles that patients should take along to hospital and for questions on responsibilities for children, dependent people or pets.